Meningkatkan Literasi Keuangan dan Akuntansi dalam Masyarakat - Kevin H. Tupamahu; Bryan F Manihuruk; Susi Elia Simaremare; Fiona M Tarima; Noch Lorensius Fatruan; Tiara Puspita Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Socialization activities to improve financial and accounting literacy in the community were carried out in Rumah Tiga Village, focusing on the role of financial and accounting literacy in family financial management. Rumah Tiga Village was chosen because it still needs understanding and skills about financial management and accounting to support economic development and community welfare. The methods used in this activity include practical demonstrations, surveys to the community, as well as cooperation with Rumah Tiga Village officials. The main focus of this socialization was to increase understanding of household financial management, achieving future financial goals, the importance of long-term savings, education on future investments, and emergency funds to avoid future financial difficulties. The role of accounting in recording income and expenses, preparing budgets, and understanding how to make household financial reports are important points for the community to become better at managing their finances. The implementation of this socialization activity is tailored to the needs of the village community, involving cooperation with the village government to increase understanding of financial literacy and accounting. It is hoped that this activity can provide good knowledge to the Rumah Tiga community about financial literacy and accounting in the community.